The possible involvement of oxidative stress in the oocyte ageing process in goldfish Carassius auratus (Linnaeus, 1758) - Samarin, Azadeh Mohagheghi; Samarin, Azin Mohagheghi; Østbye, Tone-Kari Knutsdatter; Ruyter, Bente; Sampels, Sabine; Burkina, Viktoriia; Blecha, Miroslav; Policar, Tomas (Scientific reports, 2019)
Decreasing egg quality following oocyte ageing is a major restricting factor for the breeding programs. The mechanisms behind this process has not yet been clarified. To examine the possible involvement of oxidative stress in the oocyte ageing process, the relative mRNA abundance of specific transcripts were determined in oocytes collected from 6 females and incubated in vitro for 18 hours post stripping at 20 °C in goldfish Carassius auratus. During the 18 hour-post-stripping ageing of the oocytes, relative mRNA levels of candidate transcripts involved in oxidative injury, mitochondrial function and stress response, cell cycles, apoptosis, reproduction and germ line speciation and developmental competence were measured by real-time PCR. None of the relative mRNA abundance of the examined genes were significantly altered through oocyte ageing. In addition, the amount of thiobarbituric acid reactive substances (TBARS), an indicator of lipid peroxidation, did not change over time following stripping. The activity of the antioxidant enzymes also remained constant during oocyte ageing. The results of the current study indicated that oxidative stress unlikely plays a role as an initiator or promotor in the progress of oocyte ageing in goldfish.
Keywords: Embryo, Nonmammalian; karas zlatý; oxidační stres; RNA, Messenger; rybí proteiny; Aging; oocyty; Fish Proteins; stanovení celkové genové exprese; Gene Expression Profiling; oxidace-redukce; Animals; ženské pohlaví; Goldfish; zvířata; stárnutí; peroxidace lipidů; Lipid Peroxidation; Oxidation-Reduction; Female; Oxidative Stress; messenger RNA; embryo nesavčí; Oocytes